Percutaneous breast implant herniation: a rare complication of miliary TB. (7th January 2015) - Dale, Adam P; Dedicoat, Martin J; Saleem, Tausif; Moran, Ed
Abstract : We describe the case of a 46-year-old female patient treated for disseminated tuberculosis (TB) infection involving the lungs, urinary tract and skin. Following initiation of antituberculous therapy, the patient's right breast implant eroded through the overlying skin and was seen to be herniating through the resulting defect. The breast implant was removed under local anaesthetic and histological analysis of the resected tissue demonstrated granuloma formation consistent with periprosthetic TB. Wound healing following implant removal was poor and future breast augmentation surgery was only considered following completion of 12 months anti-TB treatment. This case constitutes the first report in the literature of percutaneous breast implant herniation resulting from periprosthetic infection with TB. A high index of suspicion is required to ensure early detection and timely management of TB and, in cases where periprosthetic pus aspirate is sterile, mycobacterial infection must be actively excluded.